2011
DOI: 10.1089/gtmb.2011.0026
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 146a Expression in Rheumatoid Arthritis: Association with Tumor Necrosis Factor–Alpha and Disease Activity

Abstract: miRNA 146a expression is upregulated in patients with RA and may be a potentially useful marker of disease activity in these patients. Lack of overexpression of miRNA 146a in the presence of increased TNF-α in OA requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 28 publications
6
58
0
Order By: Relevance
“…summarises all of these reports to date. A recent report by Abou-Zeid et al 30 has basically completely reproduced our 2008 work demonstrating the elevated level of miR-146a in PBMC of 70 RA patients compared to 60 controls. Their data show that miR-146a expression is significantly higher in patients with RA than in those with osteoarthritis (n=45) and in controls (p<0.0001) 30.…”
Section: Aberrant Expression Of Mir-146a In Rasupporting
confidence: 83%
See 1 more Smart Citation
“…summarises all of these reports to date. A recent report by Abou-Zeid et al 30 has basically completely reproduced our 2008 work demonstrating the elevated level of miR-146a in PBMC of 70 RA patients compared to 60 controls. Their data show that miR-146a expression is significantly higher in patients with RA than in those with osteoarthritis (n=45) and in controls (p<0.0001) 30.…”
Section: Aberrant Expression Of Mir-146a In Rasupporting
confidence: 83%
“…A recent report by Abou-Zeid et al 30 has basically completely reproduced our 2008 work demonstrating the elevated level of miR-146a in PBMC of 70 RA patients compared to 60 controls. Their data show that miR-146a expression is significantly higher in patients with RA than in those with osteoarthritis (n=45) and in controls (p<0.0001) 30. In patients with RA, miR-146a positively correlates with tumour necrosis factor (TNF) α (p=0.0003) and disease activity monitored by the erythrocyte sedimentation rate (p=0.022) and the disease activity score in 28 joints (p=0.009) 30…”
Section: Aberrant Expression Of Mir-146a In Rasupporting
confidence: 83%
“…RA is a complex disease involving the interplay among multiple mediators and pathways of inflammation and bone damage. The expression of these mediators and their interactions in turn are controlled by a variety of regulators, including micro-RNAs (miRNAs) [5,6,7]. While current therapies offer a diverse choice of drugs for RA patients, only 50–60% of these patients respond to them [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…In RA, miR-146a and miR-155 are among the most studied miRNAs [27]. It has been reported that miR-146a is increased in RA in serum, peripheral blood, CD4 + T cells, and synovial tissue [5,27,28,29]. However, a reduction in miR-146a in RA fibroblast-like synoviocytes (FLS) has also been reported, implicating this miRNA in anti-inflammatory effects on FLS [6].…”
Section: Introductionmentioning
confidence: 99%
“…miR-146a is a relatively well known miRNA in inflammatory autoimmune diseases [14, 15]. Studies have indicated that miR-146a plays an important role in the pathogenesis of several autoimmune disorders, such as rheumatoid arthritis, systemic lupus erythematosus, and multiple sclerosis [16-18]. miR-146a was also proven to be associated with the development of autoimmune thyroid diseases [19, 20].…”
Section: Introductionmentioning
confidence: 99%